2018
DOI: 10.1016/j.jor.2018.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Growth modulation for coronal deformity correction by using Eight Plates—Systematic review

Abstract: Growth modulation with 8-plates has high efficacy and low complications for deformity correction; and has been used widely across all paediatric age groups and aetiology. The literature is mostly retrospective and heterogeneous to develop age and aetiology specific recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 17 publications
2
38
0
10
Order By: Relevance
“…In all, 94.06% (95/101) of the genu angular deformities were corrected to standard lower limb alignment (centre of the mechanical axis zone: -1 to 1). Kumar S et al [ 9 ] and Danino B et al [ 15 ] found that the deformities were successfully corrected in 196 out of 215 patients (91.2%, mean age: 9.5 years old) and 342 out of 372 physes (92%, mean age: 12.5 years old), respectively. Our research suggested that younger children with genu angular deformities could have good results when TH surgery is performed using eight-Plate implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In all, 94.06% (95/101) of the genu angular deformities were corrected to standard lower limb alignment (centre of the mechanical axis zone: -1 to 1). Kumar S et al [ 9 ] and Danino B et al [ 15 ] found that the deformities were successfully corrected in 196 out of 215 patients (91.2%, mean age: 9.5 years old) and 342 out of 372 physes (92%, mean age: 12.5 years old), respectively. Our research suggested that younger children with genu angular deformities could have good results when TH surgery is performed using eight-Plate implants.…”
Section: Discussionmentioning
confidence: 99%
“…Temporary hemiepiphysiodesis (TH) has gradually become a widely used procedure for these patients [ 1 , 6 , 7 ]. At present, the eight-Plate implant suggested by Stevens [ 8 ] is the most popular implant used for TH surgery because of the simplicity of the operation, the safety of the implant and the low rate of complications [ 1 , 9 ]. However, most studies advocate delaying TH until 8–10 years of age due to concerns about permanent physeal damage or the occurrence of rebound [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 1933, Phemister described a procedure that made premature physeal closure and arrested the growth plates on both medial and lateral sides of the bone to treat deformity (12,13). Genu valgum is an angular deformity in which the mechanical axis is shifted laterally and commonly presents in children (1,5). Growth modulation is an attractive and accepted method to use in skeletally-immature patients.…”
Section: Discussionmentioning
confidence: 99%
“…Growth modulation is an attractive and accepted method to use in skeletally-immature patients. Besides, it should be employed when failing to reach adequate correction (4,5,14). Temporary hemiepiphysiodesis is an invasive method and the basis of treatments for lower extremity angular deformities (15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation